Conceptual design of glass recycling machine - Muhamad Edham, Saharudin (2012)
The thesis present about the development of a glass recycling machine. The objectives of this project are to study about the methodology of developing a glass recycling machine by using manufacturing approaches such as design of drawing and simulation of glass recycling machine. This project is using SolidWork 2007 in order in designing the drawing and simulation testing. The materials chosen to develop the glass recycling machine is AISI 1020 with its yield strength 295 x 106 N/m2. The machine simulation is using von Mises measurement in order to determine the strength of machine. The design of drawing is made after completing the simulation analysis. As the conclusion, the machine need to be designed in drawing and simulation analysis could helps in order to further the study until prototyped and published to the public.